1669 Peripherally Inserted Central Catheter (PICC) Related Superior Vena Cava Syndrome Post Patent Ductus Arteriosus Ligation. (October 2012) - Boyle, M; Cotter, M; McCallion, N; Corcoran, D; Foran, A
Abstract : Background and Aims: To assess incidence, management and outcomes of Superior Vena Cava (SVC) syndrome in post PDA ligation patients in the Rotunda Hospital. PICC's are used routinely in postoperative paediatric cardiac patients. Following placement, catheter-related thrombosis occurs in 8% to 45% of paediatric patients. Although uncommon, resultant SVC syndrome significantly complicates management of premature infants. Methods: A retrospective chart review of infants undergoing PDA ligation from July 2011 to March 2012. Results: 5 patients had PDA ligation within the study period. Average gestation at birth was 25+4 weeks and average birth weight was 0.754kg. Surgery was performed at an average weight of 1.027kg and 26.8 days. 9 PICC lines were inserted; mean of 1.8 per patient with removal following a mean of 12.5 days. 2 cases of catheter related thrombosis, post PDA ligation, resulted in SVC obstruction. Both patients had a PICC in situ at the time of surgery, the other 3 patients did not have PICC access during surgery. SVC thrombosis was detected at a mean of 15 days post operatively. One affected patient died subsequently due to complications. Conclusions: Post-surgical catheter related thrombosis is well documented. SVC syndrome can infrequently result as a complication, which may cause severe respiratory compromise leading to high morbidity and mortality. As treatment of SVC syndrome is very difficult, especially in post operative patients and with a trend towards fewer PDA ligations, increased awareness in neonatal units may allow early diagnosis and thrombolytic therapy to prevent the progression of this syndrome.